2016
DOI: 10.1558/jsrnc.v10i3.29011
|View full text |Cite
|
Sign up to set email alerts
|

The Greening of Religion Hypothesis (Part Two)

Abstract: Herein we provide a comprehensive review of research pertinent to Lynn White, Jr's contentions in 'The Historical Roots of Our Ecologic Crisis'(1967) about the negative environmental impacts of 'Judeo-Christian' ideas as well as subsequent claims that the world's predominant religions are becoming more environmentally friendly. Definitive conclusions are difficult given the complexity of biocultural systems; nevertheless, extant research has identified many themes and dynamics that hinder environmental underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 0 publications
4
77
0
1
Order By: Relevance
“…While some cultures respect (holy) cows or worship trees (Sponsel 2014), other communities can be cruel to animals and indifferent to this-worldly environmental concerns (Taylor 2010(Taylor , 2013Taylor et al 2016). Learning to 'love' or respect one's own tribe does not mean loving animals (or sacred forests and places).…”
Section: Fourth: Self-love Can Just Be Selfishmentioning
confidence: 99%
“…While some cultures respect (holy) cows or worship trees (Sponsel 2014), other communities can be cruel to animals and indifferent to this-worldly environmental concerns (Taylor 2010(Taylor , 2013Taylor et al 2016). Learning to 'love' or respect one's own tribe does not mean loving animals (or sacred forests and places).…”
Section: Fourth: Self-love Can Just Be Selfishmentioning
confidence: 99%
“…As literature reviews document, the bulk of research on religion and the environment has been situated in the United States (Berry 2017; Taylor, Van Wieren, and Zaleha 2016). Yet recent research suggests that the empirical regularity found in the environmental attitudes of U.S. evangelicals might be linked to the national context.…”
Section: Introductionmentioning
confidence: 99%
“…Could evangelicalism support proenvironmental attitudes outside the United States, where subcultural factors that delegitimize Christian environmental concern are not operative? At present, it is hard to know, because even studies that look beyond the United States have mostly studied the Anglophone or North Atlantic world (Berry 2017; Taylor, Wieren, and Zaleha 2016), or instead relied on cross‐country data to assess the validity of the Lynn White thesis (e.g., Chuvieco, Burgui, and Gallego‐Álvarez 2016; Hagevi 2014; Hayes and Marangudakis 2000; Schulz, Zelezny, and Dalrymple 2000). As a result, the question of whether different contexts could encourage lay adherents from the same tradition to interpret theology differently has not yet been satisfactorily answered.…”
Section: Introductionmentioning
confidence: 99%
“…On the positive side, this critique at least agrees that beliefs make a difference to the way we treat the earth. It has often been pointed out since that correlations between belief and behaviour are not straightforward (e.g., (Taylor et al 2016;Taylor 2001, p. 279)), yet Christians have been spurred to think seriously about their faith and its implications. What is perhaps surprising is the degree to which environmentally-aware Protestants and Roman Catholics, especially the former, have accepted the negative assessment of Christian tradition, so that the widespread 'greening' of denominations and congregations often presents itself as a radical revision of traditional church practice and even doctrine (Heckscher 2013, pp.…”
Section: Introductionmentioning
confidence: 99%